IMPLEMENTASI ABSENSI ONLINE BERBASIS SISTEM GPS PADA PEGAWAI LAPANGAN DP5A - Noviana Seran; Stefanus D.I. Mau; Mitra Permata Ayu (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
In today’s age of technology, all activities can be performed effectively. One of the processes of absence.The process of absence of a field officer at the office of DP5A and KB of the western axis district still applies the manual process by performing a paraph as a sign of a daily presence in the process of the employee's work activity.This may cause damage or loss of data from an officer.This can also interfere with the effectiveness of a field officer’s work time process that will take place due to the time-consuming distance from each point of the area and it is not easy to come in the morning before performing the activity and return again in the afternoon to perform an absence at the dp5a office.Therefore, the author will provide solutions such as an online absence application to make the process of absence more efficient and minimize time.The method used in this study is the Agile Development Life Cycle (sdlc). which is involved in the process of making applications applied the method gradually and gradually to the desired destination..The result of this research is that field staff dp5a is more time-consuming absenteeship than a manual absence due to an online absence can be accessed from a smartphone with an existing gps feature to know the location points according to the task area.